INFLUENCE OF GROWING TECHNOLOGY ELEMENTS ON THE RYEGRASS PERENNIAL DENSITY DYNAMICS - T. Sladkovskа; V. Moisiienko (Наукові горизонти, 2019)
On the basis of research on the ryegrass perennial (Lolium perenne L.) seed cultivation, were analysed weather conditions and elements of cultivation technology for duration of interphase periods and grass density dynamics. Atmospheric precipitation over the years of research was rather irregular. In May and July 2014, there was its significant surplus of 194 and 118 mm respectively, and in 2015, on the contrary, in June and July there was a rather significant shortage of rainfall compared with the average perennial indicators: only 73 and 34 mm respectively. The temperature regime in the years of research was also not sufficiently favorable. Especially in June 2015, the average monthly temperature significantly exceeded perennial indexes by 7.2° С. Excess of these indicators was also observed in June and July 2013 and 2014 on average by 2.4 and 2.6 ° С, respectively. Our research found that the spring regrowth phase began in 2013 at the end of the first decade of April, during 2014–2015 in the third decade of March. Depending on the weather, the difference in regrowth over the years was 16 days. The growth of plants in 2013 occurred later in comparison with other years. However, the period from regrowth to harvesting was shorter and lasted 98 days for Andriana-80 and Svyatoshinsky varieties of perennial ryegrass. The progress of perennial grasses is determined by the amount of precipitation, air temperature, mineral nutrition, species and varietal composition of herb fields. It has been established that the average duration of spring regrowth-harvesting period for ryegrass perennial during the years of research on average was in the Svyatoshinsky variety – 109 days, and Andriana-80 variety – 108 days. The largest grass density of ryegrass perennial was observed with adding N60P60K60 + RCT, which is 9% more than in the N60P60K60 version. Adding the N60P60K60 compared with control increased the sowing density by an average of 55%, and only P60K60 increased it by 16%. Andriana-80 sowing density grade was 8% higher than the grade Svyatoshinsky, but the yield of seed plants was 0.52 and 0.61 /ha, respectively. Adrian sowing density was 8% higher than the Svyatoshinsky, but the yield of ryegrass perennial seeds was 0.52 and 0.61 t / ha, respectively.